(3GdbGFe HGdEJUGd aj ehGbY GdUMa GdEdcJQhfjI (B:s (3OQGSI aj GdCOGA Gdegfj h GdYhGed GdeDKQI Ydjg (B/s - (3YHO GdHOQGf, CSeGA UGdMs ((3GdbGgQI (B-(3eUQ (B:s (3GdecJH GdYQHj ddeYGQa ,s, 2020)
(3jCJj gPG GdcJGH djJfGhd YHQ aUhdg h eHGMKg ehVhY GdGOGA Gdegfj ddbGFe HGdGJUGd aj GdUMa GdEdcJQhfjI h GdYbHGJ GdJj JhGLgg h GdYhGed GdeDKQI Ydjg GP Jcef eTcdI dGdOQGSI GdJj jfGbTgG gPG GdcJGH aj GdJYQa Ydi bhI h VYa GdegGQGJ GdJj jeJdcgG GdbGFe HGdGJUGd aj ehGbY GdUMa GdGdcJQhfjI GdYQGbjI h eGjecf Gf jJYQV dg ef GdVZhW JDKQ aj GOGFg Gdegfj ShGA cGfJ VZhW SjGSjI Gh GLJeGYjI Gh GbJUGOjI Gh GdVZhW GdegfjI GdNGUI HWHjYI GdYed GdUMaj h cPdc GdYhGed GdJj JDKQ Ydi Jdc GdegGQGJ NUhUG GfgG Gge SeI jJeJY HgG Gdegfj dPG aGf eTcdI GdOQGSI JMOO aj eGgjI GdYhGed GdeDKQI Ydi GdGOGA Gdegfj ddbGFe HGdGJUGd HehGbY GdUMa GdYQGbjI h OhQgG JWhjQ Jdc GdehGbY h HPdc JGJj GdGgejI GdYdejI dgPG GdcJGH aj fOQI GdOQGSGJ GdJj QcRJ Ydi GdYhGed GdeDKQI ddbGFe HGdGJUGd aj ehGbY GdUMa GdGdcJQhfjI GdYQGbjIs
Keywords: (3GdUMa GdEdcJQhfjIs; (3GdbGFe HGdEJUGds; (3ehGbY GdUMa GdEdcJQhfjIs